Documenting Nature, Constructing Meaning: A Qualitative Case Study of Inquiry-Based Science Learning Integrated with Video-Based Environmental Observation to Foster Critical Thinking in Elementary Education - Jeane Kalengkongan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore how inquiry-based elementary science learning integrated with video-based environmental observation supports the development of students’ critical thinking. A qualitative case study design was employed involving fifth-grade students at a public elementary school located in the Lake Tondano area of North Sulawesi, Indonesia. The learning intervention was structured as a project in which students documented lake ecosystem observations through short videos and presented their findings during classroom discussions. Data were collected from student-produced videos, classroom observations, group interviews with students, teacher interviews, and researchers’ field notes. The data were analyzed using an inductive thematic approach to identify patterns of critical thinking and students’ processes of scientific meaning-making. The findings reveal that inquiry-based video projects enabled students to develop a more concrete and contextual understanding of ecosystems through direct observation, interpretation of local environmental conditions, and construction of causal explanations grounded in visual evidence. Moreover, video documentation and collaborative discussion fostered inquiry-oriented questioning, metacognitive reflection, and awareness of environmental responsibility. These results indicate that integrating inquiry-based learning, local environmental contexts, and simple video production serves as an effective pedagogical approach for fostering elementary students’ critical thinking and contextual scientific literacy.